Pengaruh Kompensasi dan Disiplin Terhadap Kinerja Karyawan Pada Kantor PLN Kota Bandar Lampung - nanda pramana putra; susi indriyani; rina lolyana (Jurnal Manajemen dan Bisnis (JMB), 2020)
AbstractThe purpose of this research is explanatory (explanatory research), which examines three variables that explain the effect of compensation and discipline on employee performance at the PLN office in Bandar Lampung. Methods of data analysis using quantitative descriptive data. Quantitative descriptive analysis is used to analyze statistically in order to test the research hypothesis on the data obtained by calculating it using SPSS software. The sample was taken as much as the population of employees at the PLN office, namely 58 employees.From the results of data processing, it has been found that the answer to the hypothesis is as follows: there is an effect of compensation on employee performance, with a level of influence (R-square) of 33.9%. There is an influence of work discipline on employee performance with an influence level of 30.8%. There is an effect of compensation and work discipline together on employees with a level of influence of 35.1% Keywords: Compensation, Discipline and Employee Performance.